Epilithic Microalgae Isolated from Biofilm on Borobudur Temple Stone - Debora Christin Purbani; Ade Lia Putri; Moh. Habibi (Journal of Tropical Biodiversity and Biotechnology, 2020)
Borobudur Temple is a historical heritage building located in an open area and made of porous building materials (stone materials). This condition makes the Borobudur Temple susceptible to various problems related to degradation and weathering. Biodeterioration of Borobudur Temple may be caused by activities of living organisms present in the biofilm of stone. Continuous monitoring and evaluation need to be carried out by observing and isolating the growth of micro-organisms, including epilithic microalgae. Therefore, this study aims to isolate and identify epilithic microalgae from the biofilm on Borobudur Temple stones. Epilithic microalgae were isolated to obtain a uni-algae and maintained under culture conditions. The morphological of microalgae were observed using light microscopy, while the 18S rRNA gene sequence determined the molecular identification of microalgae for eukaryotic and 16S rRNA sequence for prokaryotic. A total of nine epilithic microalgae were successfully isolated from the biofilm of Borobudur Temple stones. The isolated were identified as Ankistrodesmus falcatus, Tetraselmis cordiformis, Pseudendoclonium arthropyreniae,  Anabaena cylindrica,  Nostoc gelatinosum, Oscillatoria limnetica, Messastrum gracile, Stigeoclonium aestivale, and Scenedesmus acuminatus. This is the first study for the identification of microalgae from Borobudur temple stones. The isolates will be collected and will be used as a source for further study.